Isolated congenital cardiac diverticulum originating from the left ventricular apex: Report of a pediatric case - Fahrettin Uysal; Ozlem Mehtap Bostan; Muhammed Hamza Halil Toprak; Isik Senkaya Signak; Ergun Cil (Wolters Kluwer Medknow Publications, 2016)
Congenital ventricular diverticulum is a rare cardiac anomaly defined as a localized protrusion of the ventricular free wall. Although, it is usually asymptomatic, complications such as embolism, infective endocarditis, and arrhythmias can occur. The diagnosis can be made by echocardiography, cardiac magnetic resonance imaging, or catheter angiography. Surgical resection is the treatment of choice in symptomatic patients, whereas the management of asymptomatic patients often represents a therapeutic dilemma. We report here, a 9-month-old patient with asymptomatic congenital left ventricular (LV) diverticulum associated with epigastric hernia.